The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2000
DOI: 10.1080/00103620009370490
|View full text |Cite
|
Sign up to set email alerts
|

Longevities and nitrogen, phosphorus, and potassium release patterns of polymer‐coated controlled‐release fertilizers at 30°C and 40°C

Abstract: The weekly nitrogen (N), phosphorus (P), and potassium (K) release from 17 polymer-coated controlled-release fertilizer (CRF) formulations of Nutricote, Apex Gold, Osmocote, and a 9-month Macrocote were measured at 30.6±0.8°C and 40.0±1.5°C. Five grams of each CRF were placed at a depth of 50 mm in 280x50 mm acid washed then rinsed silica sand columns which were leached with deionized water three times each week until nutrient recovery ceased. The volume of leachate was recorded each week and subsampled for am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
1
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 19 publications
4
61
1
4
Order By: Relevance
“…However, by this G-CRF, both temperature and soil moisture were main factors to affect nutrient release rate which would affect dispersion of fertilizer granules, effective cross section area of ion diffusion, and other physical/chemical processes in soil. In fact, by the CRFs in which a physical barrier controls the release easily affected by both soil moisture and temperature, such results have been tested in some studies and indicated that the nutrient releases rates of CRFs increased with improvement of the soil moisture and temperature [29][30][31][32]. In this experiment, the G-CRF showed obviously delaying release effects when soil moisture and temperature were below 45% (w/w) and 35 ∘ C, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, by this G-CRF, both temperature and soil moisture were main factors to affect nutrient release rate which would affect dispersion of fertilizer granules, effective cross section area of ion diffusion, and other physical/chemical processes in soil. In fact, by the CRFs in which a physical barrier controls the release easily affected by both soil moisture and temperature, such results have been tested in some studies and indicated that the nutrient releases rates of CRFs increased with improvement of the soil moisture and temperature [29][30][31][32]. In this experiment, the G-CRF showed obviously delaying release effects when soil moisture and temperature were below 45% (w/w) and 35 ∘ C, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Since the diffusion of water into the membrane and the nutrient release is temperature dependent, as temperature increases, nutrient release of the controlled-release fertilisers also increases too (Huett and Gogel 2000;Haase et al 2007;Du et al 2008). The prolonged release period beyond the labelled rates usually found has been attributed to the fact that the release pattern of the polymer-coated fertilisers is determined in a water-leach test at constant temperature, typically 21-25°C (Haase et al 2007), conditions that are quite different to that found in the field.…”
Section: Agronomic Performances Of Fertilisersmentioning
confidence: 99%
“…With intense rain, the nutrients accumulated in the substrate are washed into the environment (Million et al, 2010). Most studies on the use of CRF have been carried out under laboratory conditions and/or without interaction with plants, or in greenhouses, where there is no interference from precipitation (Hershey & Paul, 1982;Niemiera & Leda, 1993;Cabrera, 1997;Huett & Gogel, 2000;Oliet et al, 2004;Merhaut et al, 2006). The variety of results in the literature on the composition Effects of climate and fertilization strategy on nitrogen balance in a potted crop…”
Section: Introductionmentioning
confidence: 99%